Changes in the zinc content of selected bangladeshi rice varieties through modified parboiling and milling methods (SAARC Journal of Agriculture, 2018)
Zinc deficiency is prevalent among women and children in Bangladesh, and methods to increase the zinc content of parboiled rice could contribute to its prevention. We quantified the effect of modified parboiling conditions on zinc content and of the degree of milling on zinc and phytate contents of Bangladeshi rice varieties. Parboiling studies varied the conditions used in the local commercial operations, including pre-steaming and soaking times, change of soaking water, and steaming pressure. Milling studies used 10 Bangladeshi varieties at 0% (brown), 2%, 4%, 6%, 8%, and 10% degree of milling. With ambient soaking water, shorter soaking time was observed with a higher zinc content in brown rice, but not in 10% milled rice, and changing soaking water did not modify zinc content in brown or 10% milled rice. Pre-steaming time and open- vs. closed-system steaming had no significant effect on brown or 10% milled rice zinc content. Reducing the degree of milling from 10% to 6% or 4% resulted in a mean increase in zinc content of 27% and 47%, respectively, and an increase in phytate content of 35% and 72%, respectively. Zinc content in milled rice did not appear to be significantly affected by the parboiling conditions tested. While lower degree of milling resulted in higher zinc content, it is uncertain whether the higher phytate content would fully negate this increase by decreasing the bioavailable fraction of zinc. Human studies of zinc bioavailability from Bangladeshi rice at different degrees of milling are warranted.SAARC J. Agri., 15(2): 31-43 (2017)